USM ALUMNI HAS SUSTAINABILITY CLOSE TO HER HEART - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 28 March 2016 – The concept of sustainability as instilled by Universiti Sains Malaysia (USM) was one of the things that remained deep in the heart of the USM alumna, Siti Nursyahidah Abu Bakar, 29, from Ampang, Selangor.